THE ROLE OF ACCOUNTING IN THE FORMATION OF ECONOMIC SCIENCE - ZHUK, Valeriy; ZAMLYNSKYI, Viktor; DIACHENKO, Oleksii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
This study aims to confirm the importance of accounting and the relevance of its scientific research in achieving economic development with the help of accounting information. The crisis state of almost all spheres of human activity indicates the need for qualitative analysis of management decisions in an unstructured global space. The underestimation of the role of information and analytical training as a basis for development requires adaptation of accounting content to information interests, increasing the value (understandability, appropriateness, and speed) of the process of collection, processing, maintenance, storage, and transmission of data that form modern knowledge and influence the dynamics of development. Economic growth is also possible by studying the contribution of accounting trends and scientific research to economic development. Accounting is a piece of information retrospective and prospective base, the primary source of socio-economic development strategy, and a communication language. Having access to a large mass of data, the consumer must understand its systematicity and use it responsibly because the future depends on the quality of the decisions made. High-quality accounting as a communication component strengthens the economic and social progress of the country because it is considered a tool of social and macroeconomic regulation. Accounting information should influence the integrity and sustainability of these decisions. This study explains the role of accounting research in economic development. Accounting gradually went beyond the accounting and analytical support of enterprise management. It became an essential component of economic science, the general information system of state management, and branch and global leadership.
Keywords: accounting; accounting information; information and analytical activity; economic development; retrospective accounting research